Addressing present challenges in the life-cycle of wetlands management to successfully integrate sustainability and good governance - Judita Tomaškinová; Ján Tomaškin; Hubert Theuma; Andrés F. Alcántara Valero; Vincent Attard (Journal of Environmental Engineering and Landscape Management, 2021)
The assessment of management effectiveness during the whole life-cycle process of protected areas (PAs) has become increasingly important, due to the lack of holistic background assessment work on management processes leading to a deeper knowledge of sustainable development (SD) principles. This paper aims to serve as a practical guide through a gradation model of integrated protected area management (IPAM) by carrying out an exhaustive trans-dimensional assessment of management effectiveness, identifying a critical field of activities and developing a framework mix of strategic recommendations leading to the implementation of an effective planning process. Our results could aid in the prioritisation of key decisions towards a more in-depth understanding of how to set up a balanced IPAM, as well as to enable managers and decision-makers to focus on activities that can further pre-established aims and reach the goal of five-dimensional sustainability in terms of SD and good governance.